Novel species-specific targets for real-time PCR detection of four common pathogenic Staphylococcus spp. (January 2022) - Zhou, Baoqing; Ye, Qinghua; Chen, Moutong; Li, Fan; Xiang, Xinran; Shang, Yuting; Wang, Chufang; Zhang, Jumei; Xue, Liang; Wang, Juan; Wu, Shi; Pang, Rui; et al.
Abstract: Staphylococcus aureus, S. epidermidis, S. haemolyticus, and S. hominis are important pathogenic microorganisms that cause food contamination and clinical infections. This study aimed to develop a rapid, accurate, and monitoring technique for simultaneous detection of these Staphylococcus spp. in food. A total of 19 novel candidate species-specific targets for these four Staphylococcus spp. were mined based on pangenome analysis. Four novel targets ( comFA for S. aureus, group_14348 for S. epidermidis, group_26190 for S. haemolyticus, and group_26478 for S. hominis ) were selected for quantitative polymerase chain reaction (qPCR). The limit of detection in pure culture without pre-enrichment were 10 2  colony-forming units (CFU)/mL for S. aureus, 10 3  CFU/mL for S. epidermidis and S. haemolyticus, and 10 0  CFU/mL for S. hominis, respectively. This method allowed fast, sensitive, and accurate detection of the target Staphylococcus spp. in actual samples and the presence of nontarget bacteria. The feasibility of this method was satisfying in terms of sensitivity, specificity and efficiency after evaluating 100 samples, as well as being consistent with the national standard detection method. Thus, this qPCR assay, based on novel species-specific targets, allows efficient screening for pathogenic Staphylococcus spp., and may help prevent staphylococcal contamination of food. Highlights: New species-specific gene targets were selected for pathogenic Staphylococcus spp. The functions of most species-specific genes are unknown. Pangenome analysis identified species-specific to S. hominis. A qPCR assay was developed for rapid, sensitive, simultaneous detection of four common Staphylococcus spp. The assay is useful for the detection of Staphylococcus spp. in food samples.